2021
DOI: 10.1186/s12887-021-02614-2
|View full text |Cite
|
Sign up to set email alerts
|

The severity and atypical presentations of COVID-19 infection in pediatrics

Abstract: Background Emergence of 2019-nCoV attracted global attention and WHO declared COVID-19 a public health emergency of international concern. Therefore we aimed to explore the severity and atypical manifestations of COVID-19 among children. Methods This is an observational cohort study conducted on 398 children with confirmed COVID-19 by using real-time reverse transcriptase polymerase chain reaction assay for detection of 2019-nCoV nucleic acid durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 52 publications
2
33
0
2
Order By: Relevance
“…Acute pancreatitis (1.5%) was the most common atypical presentation of COVID-19 in this study 4 . Common lab abnormalities in hospitalized patients with COVID-19 include leukopenia, lymphopenia, elevated inflammatory markers, and abnormal liver tests 4 , 5 , 6 . Mortality rates remain low in children with 0.17 per 100,000 or 0.48% of the estimated total mortality from all causes in a normal year 7 .…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…Acute pancreatitis (1.5%) was the most common atypical presentation of COVID-19 in this study 4 . Common lab abnormalities in hospitalized patients with COVID-19 include leukopenia, lymphopenia, elevated inflammatory markers, and abnormal liver tests 4 , 5 , 6 . Mortality rates remain low in children with 0.17 per 100,000 or 0.48% of the estimated total mortality from all causes in a normal year 7 .…”
Section: Introductionmentioning
confidence: 48%
“…A meta-analysis by Viner et al 3 showed children have a significantly lower susceptibility to COVID-19 infection with an odds ratio of 0.56 compared with adults. Saleh et al 4 specifically investigated hospitalized children with COVID-19 and found that the most common presentations were fever (95%), headache (60.3%), fatigue (57.8%), and shock (21.8%). Acute pancreatitis (1.5%) was the most common atypical presentation of COVID-19 in this study 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that thrombosis has a lower incidence in children with COVID-19 compared with adults ( 48 ). However, children with MIS-C are at greater risk for hypercoagulable events compared to those with asymptomatic COVID-19 infection ( 49 ) evidence of thrombosis, coronary artery involvement, or depressed ejection fraction ( < 35%) ( 18 , 36 ).…”
Section: Hypercoagulable Disease Managementmentioning
confidence: 99%
“…Ülkemizden de vakaların bildirilmeye başlaması ile pankreatit ve COVID-19 birlikteliği konusunda ilgi artmaya başlamıştır (32). Ancak araştırmamızla ilgili olarak ülkemizdeki literatürde sıklıkla olgu sunumları mevcut olup, sadece bir tane gözlemsel çalışmaya rastlanılmıştır (31).…”
Section: Covid-19 İlişkili Pankreas Hasarı Olası Mekanizmasıunclassified